Presencia del gato andino Leopardus jacobita en bosques de Polylepis de Ayacucho, Perú - Cépida-Lahuana, Ausbel (2025)
The Andean cat (Leopardus jacobita) is a felid with a restricted distribution in the high Andean regions of Peru, Bolivia, Chile, and Argentina, and is considered the most threatened member of its family in South America. Its conservation status is critical, being classified as Endangered (EN) under Peruvian legislation and on the IUCN Red List of Threatened Species. However, limited ecological information and significant knowledge gaps regarding its distribution hinder the implementation of effective conservation actions. This contribution presents the first confirmed photographic records of L. jacobita in Polylepis forests of Ayacucho Department, Peru. The results provide relevant evidence of the presence and habitat use of L. jacobita in these high Andean ecosystems, which appear to serve as vital refuges for the conservation. Furthermore, the findings highlight the need to strengthen conservation strategies in Polylepis forests, which are already affected by climate change and various anthropogenic pressures that impact L. jacobita populations both directly and indirectly. Finally, we propose the establishment of research priorities aimed at improving understanding of the species’ ecology and its role within this highly vulnerable ecosystem.